Quantifying moonlight and wind effects on flighted waterfowl capture success during night‐lighting. (18th December 2014) - Buchanan, Tore; Brook, Rodney W.; Purvis, Matthew P.; Davies, J. Chris
ABSTRACT: Night‐lighting is a common technique used to capture waterfowl, upland birds, and waterbirds. The method involves using bright artificial light and a steady loud noise to startle and confuse birds, allowing close approach and capture by hand or with a long‐handled dip‐net. Many researchers using this technique have noticed that moon phase (or relative brightness) and weather conditions can affect capture rates. Using 16 years (1996–2011) of night‐lighting capture data collected during the Ontario Waterfowl Airboat Banding Program, Canada, the effects of moon phase and wind speed on capture rates for flighted waterfowl were quantified. Increasing moon brightness had a negative effect on capture rates for all species analyzed (mallard [ Anas platyrhynchos ], wood duck [ Aix sponsa ], blue‐winged teal [ Anas discors ], green‐winged teal [ Anas crecca ], ring‐necked duck [ Aythya collaris ], hooded merganser [ Lophodytes cucullatus ], and American black duck [ Anas rubripes ]), with an increasing rate of decline in capture rates when the moon was >75% full (i.e., a bright night). Attempting waterfowl capture when the moon was >75% full led to 2‐fold cost increase per bird captured over the average cost per bird captured. Increasing wind speed was positively correlated with capture rate for some species, but had no significant effect on capture rate for most species analyzed. Night‐lighting capture of flighted waterfowl should be planned primarily during dark to moderately dark nights to maximize capture efficiency and reduce costs. © 2014 The Wildlife Society.